A different ultrastructural face of ribbon synapses in the rat retina. (23rd September 2018) - Pałasz, Artur; Mielańczyk, Łukasz; Matysiak, Natalia; Segovia, Yolanda; Savchyna, Mariia; Mordecka‐Chamera, Kinga; Worthington, John J.
Abstract: Ribbon synapses located exclusively within retinal, cochlear and vestibular connections belong to the most interesting cellular structures but their molecular nature and functions had remained unclear. The study has provided a descriptive morphological analysis of rat eye ribbon synapses using high‐resolution transmission electron microscopy (TEM). An original collection of untypical, rarely present in the literature sagittal or tangential sections through the single RIBEYE domain of the particular ribbon have been delivered.